Production of Californium-252 by Using Reverse Reaction Technology - L. Oudah, Aqeel; A. Ebrahiem, Sameera; H. Mahdi, Khalid (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
In the current work, Calculate cross sections for  252Cf (α,3n)253Fm  reaction Use of interpolation and cross-section sampling published in the international literature to select the appropriate interaction of ground-level energies in a computer-based program (MATALAB-17.0) , in steps of energies (0.2 Million electron volts). Given the importance of the 252Cf isotope and its entry into the industrial and medical fields, there was a need to determine the energy of the incident neutron to produce this isotope, relying on the masses of the entering and leaving particles and the values ​​of angular momentum to obtain an equation and according to the theory of the opposite reaction. The reaction cross sections (253Fm (3n,α) 252Cf) were calculated using the opposite reaction theory for the energy range (3.9789-14.538)MeV. The results show that the probability values increase with the neutron's energy smoothly. The results show that cross-section values are almost constant for the energy range limited to (8.5-14)MeV. The results were plotted and tabulated using MATLAB 17.0. Also, the values ​​obtained for the reaction cross sections 253Fm (3n,α) 252Cf through which the CF is produced. Semi-empirical equations were obtained for the relationship between energy and cross-section.